2022
DOI: 10.3389/fnut.2022.894278
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Succinate Impacts the Nutritional Metabolism, Protein Succinylation and Gut Microbiota of Zebrafish

Abstract: Succinate is widely used in the food and feed industry as an acidulant, flavoring additive, and antimicrobial agent. This study investigated the effects of dietary succinate on growth, energy budget, nutritional metabolism, protein succinylation, and gut microbiota composition of zebrafish. Zebrafish were fed a control-check (0% succinate) or four succinate-supplemented diets (0.05, 0.10, 0.15, and 0.2%) for 4 weeks. The results showed that dietary succinate at the 0.15% additive amount (S0.15) can optimally p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…Furthermore, we found that the addition of succinate promoted pig fat deposition, especially subcutaneous fat and intramuscular fat content. Consistent with our results, the addition of 0.15% succinate to the zebrafish diet promoted the increase in crude protein, crude fat, and energy and significantly altered the growth and development of zebrafish [20]. A study of succinate in rats found that feeding sodium succinate increased energy expenditure but did not affect dietary intake and that succinate could enter the body as a substrate [28].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, we found that the addition of succinate promoted pig fat deposition, especially subcutaneous fat and intramuscular fat content. Consistent with our results, the addition of 0.15% succinate to the zebrafish diet promoted the increase in crude protein, crude fat, and energy and significantly altered the growth and development of zebrafish [20]. A study of succinate in rats found that feeding sodium succinate increased energy expenditure but did not affect dietary intake and that succinate could enter the body as a substrate [28].…”
Section: Discussionsupporting
confidence: 88%
“…SIRT5 knockout of brown adipose tissue in mice leads to hyper-succinylation of these proteins, which in turn leads to mitochondrial respiratory impairment, defective mitophagy, and lipid metabolic disorder [19]. Recent reports have revealed that dietary disodium succinate regulates lipid synthesis, gluconeogenesis, and glycogen synthesis in intestinal, liver, and muscle tissues, thereby inhibiting protein degradation in tissues, increasing fat deposition, and improving glucose tolerance [20]. Mechanistically, it works by regulating the levels of succinylation of the tricarboxylic acid cycle and fatty acid degradation-related proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, further investigations will be imperative to explore the potential of succinate supplementation once the pathology is already established. In addition, studies on zebrafish, an appealing model for obesity and type 2 diabetes, have yielded deleterious outcomes concerning weight gain, hepatic fat accumulation and gut microbiota composition [ 75 ], which points to potential species differences.…”
Section: Strategies For Manipulating the Succinate–sucnr1 Axis In The...mentioning
confidence: 99%
“…Mechanisms for succinylation: On one hand, succinylation could be processed via non-enzymatic manners, which relies on succinyl-CoA or succinate from mitochondrial and peroxisome sources[ 4 , 5 , 10 - 14 ]. Succinylation would occur if provided with sufficient succinyl-CoA[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Succinate entering the cells could be converted to succinyl-CoA to enhance lysine succinylation[ 1 ]. A study has shown that dietary succinate increases the succinylation of intestinal and hepatic proteins with a molecular weight of 25-35 kD in zebrafish[ 14 ].…”
Section: Introductionmentioning
confidence: 99%